Juvenile hormone modulates hydrocarbon expression and reproduction in the german wasp Vespula germanica - da Silva, Rafael Carvalho; do Nascimento, Fabio Santos; Wenseleers, Tom; Oi, Cintia Akemi (Frontiers in Ecology and Evolution, 2022)
Juvenile hormone (JH) affects multiple physiological traits in insects. In social insects, besides development, JH has been demonstrated to influence caste determination and the production of chemical compounds. In social wasps, JH triggers behavioural maturation, gonadotropic effects, and hydrocarbons modulation. Here, we investigated whether JH displays the same function, previously shown in Vespula vulgaris, in females of the German wasp Vespula germanica. By experimentally treating workers with JH-analogue, an anti-JH, and acetone, we tested whether JH modulates the cuticular chemical expression (CHCs), the Dufour gland chemical composition, and hence the compounds found over the egg’s surface. Additionally, we explored whether JH has a gonadotropic effect on workers. Workers treated with the JH-analogue acquired a chemical profile that made them resemble the queen. Interestingly, the same pattern was also seen in the Dufour glands and eggs, although more subtle. Furthermore, workers treated with the JH-analogue were more fertile than compared to the controls, supporting the fact that JH indeed acts as a gonadotropic hormone. Our results indicate a similar function of JH in the societies of related species V. germanica and V. vulgaris.